THE EFFECT OF FIRM SIZE, PROFITABILITY AND PUBLIC OWNERSHIP STRUCTURE ON INCOME SMOOTHING AFTER THE IMPLICATION OF PSAK 50 AND 55 - Achmad Tezar Pahlevi Stefannandra; Negina Kencono Putri; Wita Ramadhanti; Rasyid Mei Mustofa (Jurnal Riset Akuntansi Soedirman (JRAS), 2022)
PSAK 50 & 55 (revised) is important for the banking sector, as it aims to increase transparency, reducing disclosure that only benefit for banking managerial and narrow down the possibilities of fraud. Income smoothing is one form of fraud that management is often done to maximize the benefits for themselves, so that make any investor incorrect in making decisions for their investment. This study is a verification to test the truth of knowledge and previous research on banking companies listed on the IDX. This study takes the title: "The Effect of Firm Size, Profitability and Public Ownership Structure On Income Smoothing After The Implementation Of PSAK 50 & 55" (Case Study on Banking Companies Listed on the Indonesia Stock Exchange Period 2010-2014). The population in this study are all banking companies listed on IDX in 2010-2014. This study used 25 banking companies as samples obtained through purposive sampling method. Discretionary Accrual by Modified Jones used to determine income smoothing practice. Multiple Linear Regression method used to test the effect of independent variables and the dependent variable in this study. The results of the study provides empirical evidence as follows, first, firm size has no effect on income smoothing practice. Second, return on assets has no effect on income smoothing practice. Third, operating profit margin has no effect on income smoothing practice. Fourth, earnings per share negatively affect income smoothing practice. Fifth, public ownership structure positively affect income smoothing practice. The findings of this study have implications for investors to be more cautious on earnings per share and public ownership structure in the decision to invest, because both of these factors have an influence on income smoothing practice.